Salinity and water level as factors in the distribution of vegetation in the cienega of NW Campeche, Mexico - Rico-Gray, Victor; Palacios-Rios, Monica (Instituto de Ecología, A.C., 1996)
The purpose of this study was to establish if the presence of different plant associations (cattail vegetation, pure stands of Avicennia germinans, pure stands of Rhizophora mangle, mixed mangrove stands, and Rhizophora-Eleocharis association) correspond to significant differences in physical factors (surface water level, water salinity). Field work was accomplished in the ‘petenes’ (hammocks) region, along the NW coast of Campeche, Mexico. Salinity increases with the dry season, and rapidly decreases with the onset of the rains. Rhizophora stands experience the highest salinity year-round, and the cattail association the lowest. For each association, salinity was significantly higher before the rains start, compared to the end of the rainy period. Water level decreases with the dry period and increases with the rains. At the end of the rainy period, water level is significantly higher, with significant differences between associations. Plant associations studied correspond to significantly different levels of the abiotic factors considered. Results show that each community has particular conditions, and suggest that high salinities at the end of the dry period and the extended inundation period during the rains are determinant for the establishment of species in the communities.